2021
DOI: 10.1136/bmjopen-2020-046276
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of COVID-19 IgG antibodies among healthcare workers of Pakistan: a cross-sectional study assessing exposure to COVID-19 and identification of high-risk subgroups

Abstract: ObjectiveIn this study, we aimed to find the seroprevalence of healthcare workers (HCWs) of Pakistan involved in the treatment and care of patients with COVID-19.SettingThis was a cross-sectional study and total of 15 000 HCWs involved in providing services and care to the patients with COVID-19 were randomly selected from all over Pakistan.ParticipantsInformed consent was taken from all participants and were included according to inclusion and exclusion criteria. All testing was done on serum samples for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The time required for clerking, and close examination of patients to elicit clinical signs put doctors at greater risk than any other healthcare workers. This agrees with a report from Pakistan [11].…”
Section: Discussionsupporting
confidence: 93%
“…The time required for clerking, and close examination of patients to elicit clinical signs put doctors at greater risk than any other healthcare workers. This agrees with a report from Pakistan [11].…”
Section: Discussionsupporting
confidence: 93%
“…Whereas 45% of the study participants with COVID 19 were reactive for SARS-CoV-2 IgM antibody which indicates current infection to SARS-CoV-2. A study in Pakistan by Batool et al, (2021), reported a similar finding of seroprevalence of SARS-CoV-2 IgG antibody (33%) among healthcare workers [14].…”
Section: Plos Onementioning
confidence: 63%
“…The results of the current study revealed that 19.9% (n = 284/1426) of subjects were naturally infected with COVID-19, and 12% (n = 171/1426) were unsure about their status. An earlier study on 15,000 healthcare workers randomly selected from Pakistan found that 33% of the subjects tested positive for the COVID-19 IgG antibody (20). RT-PCR studies on HCW from the Netherlands and the United Kingdom showed that 11.2% and 18% of the subjects were positive for COVID-19, respectively (21,22).…”
Section: Discussionmentioning
confidence: 98%